(untitled) (Journal of the College of Basic Education, 2022)
When E. M. Forster first visited India in 1912-1913 the political scene was relatively peaceful after the many strokes of violence that had taken place few years before his visit . The violent events emanated from Curzon’s attempt to partition Bengal. The partition was a failure, and to subside the public reaction, the Indian Council passed Act of 1909 which guaranteed the Indians a seat in the higher provisional administration. The visit of king-emperor ,George V, to India in winter of 1911-1912 and his order to transfer the capital from Calcutta to Delhi was of special importance since it was an indication that England was no longer in need for a maritime escape route. 1